Evaluation Of Effectiveness And Adoption Of Walking Tractor In Case Of Amhara Region - Etsegenet Fikru (ASTU, 2021)
Walking Tractors Are Viable Alternative For Transition From Small Holder Farming To Commercial Farming And Engine Power Source For Sub-Saharan Africa Like Ethiopia. However, Most Of Walking Tractors Were Not Effectively Utilized And Adoption Of Walking Tractor Was Not Proficient. Therefore, This Study Aimed To Investigate Ineffectiveness Of The Walking Tractor In Adoption To The Targeted Areas With Its Associated Factors. Cross-Sectional Study Design Was Conducted And A Structured Questionnaires Were Prepared And A Total Of 420 Respondents Were Equally Selected From 12 Kebeles In The Four Targeted Districts. Binary Logistic Regression, One Way Anova, T-Test And Fishers Exact Test Were Used To Evaluate Factors Associated With Adoption And Effectiveness Of Walking Tractors. In This Study Finding, Factors Such As Training, Lack Of Operating Skill, Absence Of Spare Part And Maintenance Service Could Affect Both Adoption And Effectiveness Of Walking Tractor. Education Status, Land Size, Cost Of Waking Tractor And Rental Service Were Factors That Affect Adoption Of Walking Tractor. Whereas Topography, Soil Condition And Difficulty On Operation Of Walking Tractors Were Factors That Affect Effectiveness Of Walking Tractor. Participants Who Had Primary And Above Education Levels Were 42 And More Times As Well As Participants Who Had Adult Education Were 2 And More Times More Likely To Adopt Walking Tractor Than Illiterates. The Participants Who Had Land Size Of Greater Than 2Hectare Were 6 And More Times More Likely To Adopt Walking Tractor Than Those Who Had Less Than 1 Hectare Of Land. Respondents Who Gained Training About Walking Tractor Were 17andMore Times More Likely To Adopt Walking Tractor Than That Of Respondents Who Didn??T Gain Training. Participants Who Used Walking Tractor Through Rental Service Were 3 And More Times More Likely To Adopt Walking Tractor Than Those Who Didn't Use Walking Tractor By Renting. The Significant Difference In Effectiveness Of Walking Tractor Between Red Soil Type With Sand And Black Soil With P- Value 0.005 And 0.001 Respectively; The Result Indicates Walking Tractor Was Effective On Red Soil Than Sand And Black Soil Type. While The Significant Difference Between Plain Area With Hilly And Dipping Topography Were P=0.007 And P=0.002 Respectively Indicated That Topography Was One Factor That Affect Effectiveness Of Walking Tractor. There Was A Significant Difference Between Plowing Time With Farmers Who Gained Training And Who Did Not(P=0.028).Walking Tractor Is An Ideal Technology That Facilitate Modern Farming System So That Further Studies Will Conduct To Improve The Performance Based On Soil Type And Topography AsWell Adoption Of The Walking Tractor In The Region And In The Country Level At Large.
Keywords: walking tractor, adoption, effectiveness, training, maintenance and spare part